The automated traffic handbook : managing spiders, bots, scrapers, and other non-human traffic - Still, Andy (O'Reilly Media, 2018)
Automated traffic is a major factor in the modern internet, especially for website owners. Bots, spiders, and scrapers now exceed the amount of traffic from human users, and this trend is expected to continue in the number and sophistication of bot types. With this handbook, Intechnica co-founder Andy Still provides guidelines to help public-facing sites identify and manage various types of automated traffic. Some bots are beneficial, such as automated traffic triggered by direct human action, but many of them are highly profitable ventures run by organized criminal groups. Bots can negatively impact your site and your business by: Fraudulently taking advertising revenue without displaying ads to potential customers Stealing website content for competitors to use on their own sites Publishing offensive content on your comments or forum pages Accessing your users' personal data for use elsewhere Creating fake accounts to take unfair advantage of special offers Skewing analytics that would lead you to make invalid business decisions Managing and Mitigating Bots helps you determine which traffic is non-human and requires action, and then guides you through the process of defining a bot-handling policy tailored to the type of bot traffic you identify.